Housing price, bank credit, and firm innovation investment: theory and evidence from China - Ma, Yong; Jiang, Yiqing; Zhang, Hongming (Technological and Economic Development of Economy, 2025)
This paper develops a novel theoretical model to explore the impact of housing price appreciation on firm innovation investment and its interaction with bank lending. The predictions of the model are empirically tested using a comprehensive dataset of China’s A-share listed companies and 94 cities over the period 2011–2021. The findings provide robust evidence of a crowding-out effect, where rising housing prices negatively affect firm innovation investment. Moreover, the crowding-out effect is found to be less pronounced for firms with stronger debt repayment capabilities, superior R&D capabilities, or in tighter credit environments, consistent with the theoretical predictions. Further analysis indicates that the crowding-out effect becomes significant only when banks show a stronger preference for providing short-term loans or exhibit lower service efficiency. In terms of firm innovation outcomes, housing price appreciation generally reduces innovation efficiency, and this negative impact is especially pronounced for lower-quality innovation projects. First published online 19 November 2025